Eingangsbereich in Sydney (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Interior decoration; Art; Painting; Photographs; Sydney